2002
DOI: 10.1067/maj.2002.123377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of VASER-assisted lipoplasty: A pilot clinical study

Abstract: 2002;22:131-146.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 64 publications
1
40
0
2
Order By: Relevance
“…For comparative purposes, this report includes a statistical summary of complications reported in published works using first-and second-generation devices. 14 By June of 2003, when this follow-up article was submitted, our collective experience had extended to more than 400 patients, reconfirming the safety and efficacy of the Vaser device.…”
supporting
confidence: 55%
“…For comparative purposes, this report includes a statistical summary of complications reported in published works using first-and second-generation devices. 14 By June of 2003, when this follow-up article was submitted, our collective experience had extended to more than 400 patients, reconfirming the safety and efficacy of the Vaser device.…”
supporting
confidence: 55%
“…This device was capable of rapidly emulsifying fat while delivering significantly less ultrasound energy to the tissues and was associated with less blood loss 6,7 as well as a decrease in the complication rates for UAL procedures. 8,9 Despite these advances in the safety and efficacy of the third-generation devices, in 2011, plastic surgeons reported that only 20% of the liposuction procedures in the previous year were ultrasound assisted. 10 This percentage has remained relatively unchanged over the Abstract Background: Nonfocused externally applied ultrasound energy has been used extensively in the clinical setting for noninvasive body contouring on the premise that ultrasonic diathermy may have a reducing effect on adipose tissue.…”
mentioning
confidence: 98%
“…Additionally, Fodor and Watson38 directly compared UAL with SAL and supported UAL’s superiority in sculpting fibrotic areas when compared with SAL. Finally, contemporary, third-generation UAL devices such as VASER™ (Solta Medical, Hayward, CA, USA) (Figure 1), allow for greater fragmentation of adipocytes at a lower energy setting, using pulsed rather than continuous energy 9…”
Section: Current Devicesmentioning
confidence: 99%